From incoherence to mirth: neuro-cognitive processing of garden-path jokes - Mayerhofer, Bastian; Schacht, Annekathrin (Frontiers in Psychology, 2015)
In so-called garden-path jokes, an initial semantic representation is violated, and semantic revision reestablishes a coherent representation. 48 jokes were manipulated in three conditions: (i) a coherent ending, (ii) a joke ending, and (iii) a discourse-incoherent ending. A reading times study (N =24) and three studies with recordings of ERP and pupil changes (N = 21, 24, and 24, respectively) supported the hypothesized cognitive processes. Jokes showed increased reading times of the final word compared to coherent endings. ERP data mainly indicated semantic integration difficulties (N400). Larger pupil diameters to joke endings presumably reflect emotional responses. ERP evidence for increased discourse processing efforts and emotional responses, as assumed to be reflected in late left anterior negativity and LLAN modulations and an enhanced late frontal positivity (fP600), respectively, remains however incomplete. Processing of incoherent endings was also accompanied by increased reading times, a stronger and sustained N400, and context-sensitive P600 effects. Together, these findings provide evidence for a sequential, non-monotonic, and incremental discourse comprehension of garden-path jokes.